Energy Storage Management of Green Hydrogen-Integrated Microgrid - Jordan, Isaac; Ahmed Mohamed, Ahmed Haidar; Wan Azlan, Wan Zainal Abidin; MFM, Sabri (2024)
The increasing integration of renewable energy sources (RES) within microgrids presents significant energy storage and grid stability challenges. Effective energy resource management becomes crucial as the world moves towards sustainable energy solutions. This study develops a robust modelling approach for a hybrid microgrid system that uses hydrogen storage to manage energy fluctuations. The main goal is to assess how well this integrated model balances supply and demand while maintaining frequency and voltage stability under different operational conditions. In this model, hydrogen storage is combined with renewable energy resources, and droop control serves as the conventional method to maintain system performance. The model performance has been evaluated under various load conditions, disconnection events, and fault scenarios. The findings reveal that the hybrid microgrid system maintains stable frequency within the ±5% limit but the case for the voltage is different, as it drops below the 15% limit in grid-connected and off-grid mode. The implications of using hydrogen storage in combination with renewable energy resources are significant for future energy policy development. This study suggests that policymakers should consider hydrogen a critical component in energy storage solutions, enhancing grid resilience and flexibility. It promotes energy security and supports the transition to low-carbon energy systems, ultimately paving the way for a more sustainable energy landscape.